2014
DOI: 10.1111/jorc.12051
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clusters in Patients on Dialysis and Their Association With Quality‐of‐life Outcomes

Abstract: The strong associations between symptom clusters and depressive symptoms and the physical and mental domains of HRQOL should lead to an increased focus on symptom-alleviating interventions. Additional research is warranted to determine whether treatment of symptom clusters rather than single symptoms will improve HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(134 citation statements)
references
References 33 publications
7
120
2
5
Order By: Relevance
“…Some data are available on symptom clusters in patients with HIV disease (10,11), chronic kidney failure and endstage renal disease (15,16), COPD (12,13), osteoarthritis (45), rheumatoid arthritis (46), and heart failure (14). Similar to studies in oncology, the occurrence of symptom clusters in these chronic conditions is associated with decrements in functional status and QOL, as well as increased health care utilization and mortality.…”
Section: Transferability To Other Chronic Conditionsmentioning
confidence: 82%
See 1 more Smart Citation
“…Some data are available on symptom clusters in patients with HIV disease (10,11), chronic kidney failure and endstage renal disease (15,16), COPD (12,13), osteoarthritis (45), rheumatoid arthritis (46), and heart failure (14). Similar to studies in oncology, the occurrence of symptom clusters in these chronic conditions is associated with decrements in functional status and QOL, as well as increased health care utilization and mortality.…”
Section: Transferability To Other Chronic Conditionsmentioning
confidence: 82%
“…While the psychiatric literature provides excellent examples of the use of hierarchical cluster analysis to define subgroups of patients within a diagnostic subgroup (for examples, see 5-7) or as diagnostic criteria (for examples, see 8,9), the majority of the research on symptom clusters in patients with chronic conditions was conducted with oncology patients. However, an emerging body of evidence suggests that symptom clusters occur in patients with a variety of chronic conditions (eg, HIV disease [10,11], chronic obstructive pulmonary disease [COPD] [12,13], heart disease [14], end-stage renal disease [ESRD] [15,16]). Nonetheless, research on symptom clusters is extremely limited.…”
mentioning
confidence: 99%
“…Beyond foot lesions and their sequelae, peripheral neuropathy can have a debilitating effect on the quality of life and physical function, a relationship that is also evident in dialysis patients . In a study of 301 dialysis patients, neuromuscular symptoms were independently associated with reduced self‐reported physical function and increased depressive symptoms. Another study reported a significant reduction in gait speed that was negatively correlated with the severity of peripheral neuropathy and greater difficulty in activities of daily living …”
Section: Implications Of Peripheral Neuropathy In Ckdmentioning
confidence: 99%
“…Preliminary research also suggests that pain is associated with impaired HR-QOL. 45,46 Davison et al assessed pain using the Edmonton Symptom Assessment Scale and HR-QOL using the Kidney Disease Quality of Life Short Form (KDQOL-SF) on two occasions 6 months apart among 591 patients on chronic dialysis. 45 Similar to the SF-12 used in the current study, the KDQOL-SF generates PCS and MCS scores ranging from 0 to 100.…”
Section: Sacks Et Al Assessed Depression and Hr-qol With The Beck Dementioning
confidence: 99%